Pendampingan Pembuatan Konten dan Publikasi Gerakan Sosial bagi Anggota Remaja Masjid - Khoeroni, Ulfah Siti; Nurhadi, Zikri Fachrul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Ikatan Remaja Masjid Suci (IRMAS) has a variety of social movements of productive and positive activities that should be published in order to be an inspiration and motivation for its neighbors or a large audience. The problem faced by Ikatan Remaja Masjid Suci (IRMAS) is the limitation in using digital media effectively to spread messages of social movements. The limited knowledge and skills in creating interesting content as well as appropriate publication strategies have hampered community efforts to disseminate social movement activities in reaching a wider target audience and affecting the growth of positive movements in society. The aim of this support program is to enhance the capacity and skills of community members in creating, managing and generating effective content on social media platforms especially social media instagram. The implementation method is three-stage: the first stage is conducting community surveys, the second is applying for permits and the third stage is implementation and support. The result of the accompanying program is the formation of a team of graphic designers, videographers, content writers and social media specialists, through a team that has been formed, the accompanying program has produced output of work on social media instagram Ikatan Remaja Masjid Suci reviewed from the activities during the accompaniment, the activities are going according to the expected plan, so that the accompanying program has a long-term impact the community must prepare cadres to continue the creation of content and publication of the community social movement.